Spatial Insurance of Distinct Ecological Functions - N. Mouquet; L. Mahaut; W. Thuiller; A. Auber; N. Casajus; B. J. Enquist; P. Gaüzère; N. Loiseau; D. Mouillot; F. Munoz; S. Villéger; C. Violle (Ecology Letters, 2025)
Biodiversity can buffer ecosystem functioning against disturbances by allowing species to compensate for the functions lost through the extirpation of other species, a key process known as ecological insurance. Functional ecology has extended this idea by emphasising trait redundancy amongst species that help buffer core ecosystem functions. However, some functions might be supported only by species with distinct combinations of trait values, which are less likely to be redundant within local communities. Here, we present a new and widely applicable framework to quantify the spatial insurance of locally functionally distinct species amongst communities. Our framework characterises how communities can disproportionately insure (functional sources) or depend on (functional sinks) neighbour communities, a dual relationship that is not captured by traditional metrics of functional beta diversity. We illustrate the application of our framework at broad spatial scales for plants and birds, highlighting biogeographic patterns of functional sources and sinks. This trait‐based spatial perspective reveals functional vulnerability, as illustrated by bird communities where functional sources were disproportionately impacted by human activities. It also provides a new approach to identify regions that differ in potential resilience to environmental change and to inform conservation strategies grounded in spatial trait distributions, supporting the preservation of functional distinctiveness beyond a focus on local biodiversity metrics.

The ecological causes of functional distinctiveness in communities - François Munoz; Christopher A. Klausmeier; Pierre Gaüzère; Gaurav Kandlikar; Elena Litchman; Nicolas Mouquet; Annette Ostling; Wilfried Thuiller; Adam C. Algar; Arnaud Auber; Marc W. Cadotte; Léo Delalandre; et al. (Ecology Letters, 2023)
Recent work has shown that evaluating functional trait distinctiveness, the average trait distance of a species to other species in a community offers promising insights into biodiversity dynamics and ecosystem functioning. However, the ecological mechanisms underlying the emergence and persistence of functionally distinct species are poorly understood. Here, we address the issue by considering a heterogeneous fitness landscape whereby functional dimensions encompass peaks representing trait combinations yielding positive population growth rates in a community. We identify four ecological cases contributing to the emergence and persistence of functionally distinct species. First, environmental heterogeneity or alternative phenotypic designs can drive positive population growth of functionally distinct species. Second, sink populations with negative population growth can deviate from local fitness peaks and be functionally distinct. Third, species found at the margin of the fitness landscape can persist but be functionally distinct. Fourth, biotic interactions (positive or negative) can dynamically alter the fitness landscape. We offer examples of these four cases and guidelines to distinguish between them. In addition to these deterministic processes, we explore how stochastic dispersal limitation can yield functional distinctiveness. Our framework offers a novel perspective on the relationship between fitness landscape heterogeneity and the functional composition of ecological assemblages.

Links to rare climates do not translate into distinct traits for island endemics - Vanessa Cutts; Dagmar M. Hanz; Martha Paola Barajas‐Barbosa; Franziska Schrodt; Manuel J. Steinbauer; Carl Beierkuhnlein; Pierre Denelle; José María Fernández‐Palacios; Pierre Gaüzère; Matthias Grenié; Severin D. H. Irl; Nathan Kraft; et al. (Ecology Letters, 2023)
Current models of island biogeography treat endemic and non‐endemic species as if they were functionally equivalent, focussing primarily on species richness. Thus, the functional composition of island biotas in relation to island biogeographical variables remains largely unknown. Using plant trait data (plant height, leaf area and flower length) for 895 native species in the Canary Islands, we related functional trait distinctiveness and climate rarity for endemic and non‐endemic species and island ages. Endemics showed a link to climatically rare conditions that is consistent with island geological change through time. However, functional trait distinctiveness did not differ between endemics and non‐endemics and remained constant with island age. Thus, there is no obvious link between trait distinctiveness and occupancy of rare climates, at least for the traits measured here, suggesting that treating endemic and non‐endemic species as functionally equivalent in island biogeography is not fundamentally wrong.

A review of the heterogeneous landscape of biodiversity databases: Opportunities and challenges for a synthesized biodiversity knowledge base - Xiao Feng; Brian J. Enquist; Daniel S. Park; Brad Boyle; David D. Breshears; Rachael V. Gallagher; Aaron Lien; Erica A. Newman; Joseph R. Burger; Brian S. Maitner; Cory Merow; Yaoqi Li; et al. (Global Ecology and Biogeography, 2022)
Aim Addressing global environmental challenges requires access to biodiversity data across wide spatial, temporal and taxonomic scales. Availability of such data has increased exponentially recently with the proliferation of biodiversity databases. However, heterogeneous coverage, protocols, and standards have hampered integration among these databases. To stimulate the next stage of data integration, here we present a synthesis of major databases, and investigate (a) how the coverage of databases varies across taxonomy, space, and record type; (b) what degree of integration is present among databases; (c) how integration of databases can increase biodiversity knowledge; and (d) the barriers to database integration. Location Global. Time period Contemporary. Major taxa studied Plants and vertebrates. Methods We reviewed 12 established biodiversity databases that mainly focus on geographic distributions and functional traits at global scale. We synthesized information from these databases to assess the status of their integration and major knowledge gaps and barriers to full integration. We estimated how improved integration can increase the data coverage for terrestrial plants and vertebrates. Results Every database reviewed had a unique focus of data coverage. Exchanges of biodiversity information were common among databases, although not always clearly documented. Functional trait databases were more isolated than those pertaining to species distributions. Variation and potential incompatibility of taxonomic systems used by different databases posed a major barrier to data integration. We found that integration of distribution databases could lead to increased taxonomic coverage that corresponds to 23 years’ advancement in data accumulation, and improvement in taxonomic coverage could be as high as 22.4% for trait databases. Main conclusions Rapid increases in biodiversity knowledge can be achieved through the integration of databases, providing the data necessary to address critical environmental challenges. Full integration across databases will require tackling the major impediments to data integration: taxonomic incompatibility, lags in data exchange, barriers to effective data synchronization, and isolation of individual initiatives.

The dimensionality and structure of species trait spaces - David Mouillot; Nicolas Loiseau; Matthias Grenié; Adam C. Algar; Michele Allegra; Marc W. Cadotte; Nicolas Casajus; Pierre Denelle; Maya Guéguen; Anthony Maire; Brian Maitner; Brian J. McGill; et al. (Ecology Letters, 2021)
Trait‐based ecology aims to understand the processes that generate the overarching diversity of organismal traits and their influence on ecosystem functioning. Achieving this goal requires simplifying this complexity in synthetic axes defining a trait space and to cluster species based on their traits while identifying those with unique combinations of traits. However, so far, we know little about the dimensionality, the robustness to trait omission and the structure of these trait spaces. Here, we propose a unified framework and a synthesis across 30 trait datasets representing a broad variety of taxa, ecosystems and spatial scales to show that a common trade‐off between trait space quality and operationality appears between three and six dimensions. The robustness to trait omission is generally low but highly variable among datasets. We also highlight invariant scaling relationships, whatever organismal complexity, between the number of clusters, the number of species in the dominant cluster and the number of unique species with total species richness. When species richness increases, the number of unique species saturates, whereas species tend to disproportionately pack in the richest cluster. Based on these results, we propose some rules of thumb to build species trait spaces and estimate subsequent functional diversity indices.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A plant growth form dataset for the New World - K. Engemann; B. Sandel; B. Boyle; B. J. Enquist; P. M. Jørgensen; J. Kattge; B. J. McGill; N. Morueta‐Holme; R. K. Peet; N. J. Spencer; C. Violle; S. K. Wiser; et al. (Ecology, 2016)
This dataset provides growth form classifications for 67,413 vascular plant species from North, Central, and South America. The data used to determine growth form were compiled from five major integrated sources and two original publications: the Botanical Information and Ecology Network ( BIEN ), the Plant Trait Database ( TRY ), the SALVIAS database, the USDA PLANTS database, Missouri Botanical Garden's Tropicos database, Wright (2010), and Boyle (1996). We defined nine plant growth forms based on woodiness (woody or non‐woody), shoot structure (self‐supporting or not self‐supporting), and root traits (rooted in soil, not rooted in soil, parasitic or aquatic): Epiphyte, Liana, Vine, Herb, Shrub, Tree, Parasite, or Aquatic. Species with multiple growth form classifications were assigned the growth form classification agreed upon by the majority (>2/3) of sources. Species with ambiguous or otherwise not interpretable growth form assignments were excluded from the final dataset but are made available with the original data. Comparisons with independent estimates of species richness for the Western hemisphere suggest that our final dataset includes the majority of New World vascular plant species. Coverage is likely more complete for temperate than for tropical species. In addition, aquatic species are likely under‐represented. Nonetheless, this dataset represents the largest compilation of plant growth forms published to date, and should contribute to new insights across a broad range of research in systematics, ecology, biogeography, conservation, and global change science.

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Linking environmental filtering and disequilibrium to biogeography with a community climate framework - Benjamin Blonder; David Nogués-Bravo; Michael K. Borregaard; John C. Donoghue II; Peter M. Jørgensen; Nathan J. B. Kraft; Jean-Philippe Lessard; Naia Morueta-Holme; Brody Sandel; Jens-Christian Svenning; Cyrille Violle; Carsten Rahbek; et al. (Ecology, 2015)
We present a framework to measure the strength of environmental filtering and disequilibrium of the species composition of a local community across time, relative to past, current, and future climates. We demonstrate the framework by measuring the impact of climate change on New World forests, integrating data for climate niches of more than 14 000 species, community composition of 471 New World forest plots, and observed climate across the most recent glacial–interglacial interval. We show that a majority of communities have species compositions that are strongly filtered and are more in equilibrium with current climate than random samples from the regional pool. Variation in the level of current community disequilibrium can be predicted from Last Glacial Maximum climate and will increase with near‐future climate change.

Habitat area and climate stability determine geographical variation in plant species range sizes - Naia Morueta‐Holme; Brian J. Enquist; Brian J. McGill; Brad Boyle; Peter M. Jørgensen; Jeffrey E. Ott; Robert K. Peet; Irena Šímová; Lindsey L. Sloat; Barbara Thiers; Cyrille Violle; Susan K. Wiser; et al. (Ecology Letters, 2013)
Despite being a fundamental aspect of biodiversity, little is known about what controls species range sizes. This is especially the case for hyperdiverse organisms such as plants. We use the largest botanical data set assembled to date to quantify geographical variation in range size for ~ 85 000 plant species across the New World. We assess prominent hypothesised range‐size controls, finding that plant range sizes are codetermined by habitat area and long‐ and short‐term climate stability. Strong short‐ and long‐term climate instability in large parts of North America, including past glaciations, are associated with broad‐ranged species. In contrast, small habitat areas and a stable climate characterise areas with high concentrations of small‐ranged species in the Andes, Central America and the Brazilian Atlantic Rainforest region. The joint roles of area and climate stability strengthen concerns over the potential effects of future climate change and habitat loss on biodiversity.

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Plant traits related to competition: how do they shape the functional diversity of communities? - M. Navas; C. Violle (Community Ecology, 2009)

Invasive river plants from Portuguese floodplains: What can species attributes tell us? - I. Bernez; F. Aguiar; C. Violle; T. Ferreira (Hydrobiologia, 2006)